Navigating Modernization: Challenges and Strategies for Muslim Society in Indonesia - Alwin; Anantyasari, Malta (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
This study explores the challenges posed by modernization to Muslim society by employing a qualitative library research approach. Modernization, driven by the rapid development of science, technology, and globalization, has significantly transformed social, cultural, and religious life. The findings indicate that modernization has led to the erosion of religious identity among youth, weakened the practice of Islamic creed, widened the gap between Islamic traditions and modern societal demands, and created internal conflicts between conservative and progressive groups within the Muslim world. However, the literature also highlights several strategic responses, such as strengthening contextual Islamic education, promoting adaptive religious interpretation, and utilizing digital platforms for religious outreach. The study concludes that maintaining a balanced and constructive engagement with modernization is essential for ensuring that Islamic values remain relevant and influential in shaping ethical and harmonious modern societies.